The wing-to-wing coupling mechanism of Scutelleridae (Hemiptera: Heteroptera) - Czaja, Joanna (Zootaxa, 2012)
The wing-to-wing coupling mechanism of 19 species representing 19 genera of Afrotropical Scutelleridae is studied andthree types were recognized. A phylogenetic significance of the morphological modifications of these structures in Scutelleridae was briefly discussed.